Islamic Journalistic Ethics To Reduce Hoax News During The Covid-19 Pandemic - Suf Kasman; Nuryani; Monita Sholeha (Profetik: Jurnal Komunikasi, 2024)
This research aims to identify Islamic journalistic ethics in reducing the rise of hoax news during the COVID-19 pandemic and to establish standards for news eligibility free from hoaxes. The spread of hoax news has become increasingly widespread, often trending. The 2020 KIC survey revealed that nearly 60% of Indonesians are exposed to hoax news, primarily related to politics, health, and religion. In Indonesia, hoaxes distort facts by presenting convincing yet unverifiable information, exploited by irresponsible parties to instill slander and hatred. Therefore, this research seeks to examine the rise of hoaxes complicating pandemic management and how to counteract them. Data is obtained from Kompas TV. This research employs a qualitative approach with descriptive methods. The study reveals that Kompas TV journalists adhere to Islamic journalistic ethics and the Cyber Media News Guidelines, ensuring their news content is accurate and verified. During the COVID-19 pandemic, Kompas TV journalists strictly verify information. From Kompas TV's perspective, the COVID-19 pandemic has led to an abundance of hoax news that must be prevented as early as possible